PERAN GANTIBAJU.COM DALAM MENJAGA LOYALITAS E-KOMUNITAS GABAN - Hernikawati, Dewi (Kementerian Komunikasi dan Informatika R.I., 2013)
Information and Communication Technology advancement spur economic growth, one of the areas affected are the creative industries. Gantibaju.com as one of the creative industries that depend on the community. Gaban is a name for community members of Gantibaju.com. Research method used a qualitative approach by conducting in-depth interviews and observation. This research problem is how Gantibaju.com role in maintaining the loyality of the community (Gaban). The theory used are a brand community and brand loyalty. Result of this research, a communication is the most important factor to maintain community. Communication online and off line like kopi darat. Another factors are high creative, do things different, prizes were awarded, the theme is contested, the image quality t-shirt and screen printing, activity that involves community member such as Corporate Social Respone (CSR), the website of Gantibaju.com, and freedom for member of the community to follow other competition.